Transient CHO expression platform for robust antibody production and its enhanced N‐glycan sialylation on therapeutic glycoproteins. (27th October 2018) - Zhong, Xiaotian; Ma, Weijun; Meade, Caryl L.; Tam, Amy S.; Llewellyn, Eliza; Cornell, Richard; Cote, Kaffa; Scarcelli, John J.; Marshall, Jeffrey K.; Tzvetkova, Boriana; Figueroa, Bruno; DiNino, Dana; et al.
Abstract : Large‐scale transient expression in mammalian cells is a rapid protein production technology often used to shorten overall timelines for biotherapeutics drug discovery. In this study we demonstrate transient expression in a Chinese hamster ovary (CHO) host (ExpiCHO‐S™) cell line capable of achieving high recombinant antibody expression titers, comparable to levels obtained using human embryonic kidney (HEK) 293 cells. For some antibodies, ExpiCHO‐S™ cells generated protein materials with better titers and improved protein quality characteristics (i.e., less aggregation) than those from HEK293. Green fluorescent protein imaging data indicated that ExpiCHO‐S™ displayed a delayed but prolonged transient protein expression process compared to HEK293. When therapeutic glycoproteins containing non‐Fc N‐linked glycans were expressed in transient ExpiCHO‐S™, the glycan pattern was unexpectedly found to have few sialylated N‐glycans, in contrast to glycans produced within a stable CHO expression system. To improve N‐glycan sialylation in transient ExpiCHO‐S™, we co‐transfected galactosyltransferase and sialyltransferase genes along with the target genes, as well as supplemented the culture medium with glycan precursors. The authors have demonstrated that co‐transfection of glycosyltransferases combined with medium addition of galactose and uridine led to increased sialylation content of N‐glycans during transient ExpiCHO‐S™ expression. These results have provided a scientific basis for developing a future transient CHO system with N‐glycan compositions that are similar to those profiles obtained from stable CHO protein production systems. © 2018 American Institute of Chemical Engineers Biotechnol. Prog ., 35: e2724, 2019